Occult Roots of Religious Studies On the Influence of Non-Hegemonic Currents on Academia around 1900 - Zander, Helmut; Mühlematter, Yves (Okkulte Moderne, 2021)
This book focuses on the interconnections between religious studies and occultism. In addition, it explores new fields of research by introducing "biograms" of scholars whose relationship to occultism and science is sometimes known, but largely under-researched. In terms of boundry work between academic disciplines, this book argues that esotericism is an intrinsic part of hegemonic cultures.